Direct Conversion of Wheat Straw into Electricity with a Biomass Flow Fuel Cell Mediated by Two Redox Ion Pairs. Issue 3 (15th December 2016) - Gong, Jian; Liu, Wei; Du, Xu; Liu, Congmin; Zhang, Zhe; Sun, Feifei; Yang, Le; Xu, Dong; Guo, Hua; Deng, Yulin
Abstract: In this paper, a biomass flow fuel cell to directly convert wheat straw to electricity at low temperature (80–90 °C) and atmospheric pressure is presented. Two redox ion pairs, Fe 3+ /Fe 2+ and VO2 + /VO 2+, acting as redox catalysts and charge carriers, were used in the anode and cathode flow tanks, respectively. The wheat straw was first oxidized by Fe 3+ in the anode tank at approximately 100 °C. The reduced Fe 2+ in the anode was used to construct a fuel cell with VO2 + in the cathode. The VO2 + ions were reduced to VO 2+ and regenerated to VO2 + by oxygen oxidation. The wheat straw flow fuel cell showed a power output of 100 mW cm −2 . Mediated with liquid Fe 3+ carriers, the solid powder of wheat straw could be gradually degraded into low‐molecular‐weight organic molecules and even oxidized to CO2 at the anode without using noble‐metal catalysts. The overpotential for the electrodes of the flow fuel cell was examined and the energy cost was estimated. Abstract : Direct wheat straw to electricity : Two redox pairs, Fe 3+ /Fe 2+ and VO2 + /VO 2+, are applied as redox catalysts and charge carriers in anode and cathode flow tanks, respectively, to drive the flow fuel cell, which can directly degrade wheat straw powder and generate approximately 100 mW cm −2 electric power density.